4-Methylumbelliferone enhances the effects of chemotherapy on both temozolomide-sensitive and resistant glioblastoma cells - Pibuel, Matías Arturo (2023)
Glioblastoma (GBM) is the most frequent malignant primary tumor of the CNS in adults, with a median survival of 14.6 months after diagnosis. The effectiveness of GBM therapies remains poor, highlighting the need for new therapeutic alternatives. In this work, we evaluated the effect of 4-methylumbelliferone (4MU), a coumarin derivative without adverse effects reported, in combination with temozolomide (TMZ) or vincristine (VCR) on U251, LN229, U251-TMZ resistant (U251-R) and LN229-TMZ resistant (LN229-R) human GBM cells. We determined cell proliferation by BrdU incorporation, migration through wound healing assay, metabolic and MMP activity by XTT and zymography assays, respectively, and cell death by PI staining and flow cytometry. 4MU sensitizes GBM cell lines to the effect of TMZ and VCR and inhibits metabolic activity and cell proliferation on U251-R cells. Interestingly, the lowest doses of TMZ enhance U251-R and LN229-R cell proliferation, while 4MU reverts this and even sensitizes both cell lines to TMZ and VCR effects. We showed a marked antitumor effect of 4MU on GBM cells alone and in combination with chemotherapy and proved, for the first time, the effect of 4MU on TMZ-resistant models, demonstrating that 4MU would be a potential therapeutic alternative for improving GBM therapy even on TMZ-refractory patients.